Point mutation impairs centromeric CENH3 loading and induces haploid plants - Karimi-Ashtiyani, Raheleh (Proc Natl Acad Sci U S A, 2015)
The chromosomal position of the centromere-specific histone H3 variant CENH3 (also called “CENP-A”) is the assembly site for the kinetochore complex of active centromeres. Any error in transcription, translation, modification, or incorporation can affect the ability to assemble intact CENH3 chromatin and can cause centromere inactivation [Allshire RC, Karpen GH (2008) Nat Rev Genet 9 (12):923–937]. Here we show that a single-point amino acid exchange in the centromere-targeting domain of CENH3 leads to reduced centromere loading of CENH3 in barley, sugar beet, and Arabidopsis thaliana. Haploids were obtained after cenh3 L130F-complemented cenh3-null mutant plants were crossed with wild-type A. thaliana. In contrast, in a noncompeting situation (i.e., centromeres possessing only mutated or only wild-type CENH3), no uniparental chromosome elimination occurs during early embryogenesis. The high degree of evolutionary conservation of the identified mutation site offers promising opportunities for application in a wide range of crop species in which haploid technology is of interest.